SISTEM PENDUKUNG KEPUTUSAN PENERIMA BEASISWA DENGAN METODE ANALYTIC HIERARCHY PROCESS (AHP) - Miska Irani Br Tarigan; Reza Suranta Barus (UPPM, 2017)
Giving scholarships to students is done objectively. This requires a logical decision-making plan and is needed from several criteria needed. This research will approve and build support system applications for scholarship recipients. Where, the application that is built will use the VB.NET programming language and MySQL database. The criteria used were the Grade Point Average (GPA), Semester, Academic Potential Test (TPA), Interview, Parent Income. This study uses the Analytic Hierarchy Process (AHP) method, where scholarship recipients will be determined based on the highest score. Scholarships approved are BBP and PPA.